Vascular Endothelial Growth Factor Improves Physico-Mechanical Properties and Enhances Endothelialization of Poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/Poly(ε-caprolactone) Small-Diameter Vascular Grafts In vivo - Antonova, Larisa V.; Sevostyanova, Victoria V.; Kutikhin, Anton G.; Mironov, Andrey V.; Krivkina, Evgeniya O.; Shabaev, Amin R.; Matveeva, Vera G.; Velikanova, Elena A.; Sergeeva, Evgeniya A.; Burago, Andrey Y.; Vasyukov, Georgiy Y.; Glushkova, Tatiana V.; et al. (Frontiers in Pharmacology, 2016)
The combination of a natural hydrophilic polymer poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and a synthetic hydrophobic polymer poly(ε-caprolactone) (PCL) is promising for the preparation of biodegradable and biocompatible small-diameter vascular grafts for bypass surgery. However, physico-mechanical properties and endothelialization rate of PHBV/PCL grafts are poor. We suggested that incorporation of vascular endothelial growth factor (VEGF) into PHBV/PCL grafts may improve their physico-mechanical properties and enhance endothelialization. Here we compared morphology, physico-mechanical properties, and in vivo performance of electrospun small-diameter vascular grafts prepared from PHBV/PCL with and without VEGF. Structure of the graft surface and physico-mechanical properties were examined by scanning electron microscopy and universal testing machine, respectively. Grafts were implanted into rat abdominal aorta for 1, 3, and 6 months with the further histological, immunohistochemical, and immunofluorescence examination. PHBV/PCL grafts with and without VEGF were highly porous and consisted mostly of nanoscale and microscale fibers, respectively. Mean pore diameter and mean pore area were significantly lower in PHBV/PCL/VEGF compared to PHBV/PCL grafts (1.47 µm and 10.05 µm2; 2.63 µm and 47.13 µm2, respectively). Durability, elasticity, and stiffness of PHBV/PCL grafts with VEGF were more similar to internal mammary artery compared to those without, particularly 6 months postimplantation. Both qualitative examination and quantitative image analysis showed that three-fourths of PHBV/PCL grafts with VEGF were patent and had many CD31-, CD34-, and vWF-positive cells at their inner surface. However, all PHBV/PCL grafts without VEGF were occluded and had no or a few CD31-positive cells at the inner surface. Therefore, VEGF enhanced endothelialization and improved graft patency at all the time points in a rat abdominal aorta replacement model. In conclusion, PHBV/PCL grafts with VEGF have better biocompatibility and physico-mechanical properties compared to those without. Incorporation of VEGF improves graft patency and accelerates formation of endothelial cell monolayer.